مستوى جودة عناصر البرامج التربوية الفردية المقدمة للتلميذات ذوات الإعاقة الفكرية - الرميخان، شروق سليمان; القريني، تركي عبدالله سليمان (دار سمات للدراسات والأبحاث, 2019)
هدفت الدراسة الحالية إلى التعرف على جودة عناصر البرامج التربوية الفردية المقدَّمَة للتلميذات ذوات الإعاقة الفكرية، بمعاهد وبرامج التربية الفكرية، الملحقة بالمدارس العادية، في المراحل الابتدائية والمتوسطة والثانوية، في مدينة الرياض، وبلغ عدد البرامج التربوية الفردية التي تم تحليل محتواها (421) برنامجًا، وأظهرت نتائج الدراسة أن مستوى جودة عناصر البرامج التربوية الفردية ضعيفة جدًا، ممَّا يشيرُ إلى أن تقديم تلك البرامج لم يصل إلى ما تقوم عليه الممارسات العالمية في هذا الجانب، وإلى ما يطمح إليه المختصون، وأسرُ التلميذات. كما أظهرت الدراسة وجود فروق ذات دلالة إحصائية تعود إلى اختلاف المكان التربوي لصالح برامج التربية الفكرية الملحقة بالمدارس العادية، وأبرزت النتائجُ وجودَ فروق ذات دلالة إحصائية في مستوى جودة عناصر البرامج التربوية الفردية المقدَّمة للتلميذات ذوات الإعاقة الفكرية، تعود إلى اختلاف المرحلة الدراسية لصالح المرحلة الابتدائية.
The purpose of this study is to identify the quality of the Individualized Education Programs (IEPs) that are provided to female pupils with intellectual disability in educational institutes and public schools in Riyadh. The current study analyzed the content of 421 IEPs using a survey form developed and designed to address the objectives and queries of this study. The results of the study showed that the quality of the IEPs was very weak, which indicates that the implementation of these programs did not reach into the international practices in this aspect and the expectations the specialists in this field and families of these students. The results also showed statistical differences in the outcomes of the IEPs for female students with intellectual disabilities depending on the specific educational institution, with the quality of the outcomes being higher in the regular schools. In addition, student grade level was also a factor impacting IEP outcomes with IEP content at the elementary level demonstrating statistically improved outcomes compared to the older school children.
Keywords: ذوي الاحتياجات الخاصة -- الاعاقة العقلية -- جودة البرامج التربوية